Etika Bisnis Islam dalam Pelayanan Haji dan Umrah USKINU Ponorogo - Arsyadani, A. Arfinanto; Maulidia, Rohmah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article examines the implementation of Islamic business ethics in the hajj and umrah services provided by Uskinu Ponorogo, under the auspices of PCNU and PC Muslimat NU. Hajj and umrah, as both religious and economic activities, require regulations that align with sharia principles, including justice, honesty, and social responsibility. Using a descriptive qualitative approach, this study collects primary and secondary data through interviews, observations, and literature reviews to understand the application of business ethics in hajj and umrah services. The findings indicate that Uskinu emphasizes honesty, humility, commitment to keeping promises, and responsibility in its services, which not only comply with government regulations but also address the needs of the jamaah, particularly the elderly. Thus, Uskinu successfully integrates Islamic values into worship services, contributing positively to the spiritual experience of the jamaah and serving as a model for other hajj and umrah organizers in Indonesia